Metagenomic Characterization of Soil Microbial Communities from Makueni and Kiambu Counties of Kenya - Degefu, Tulu; Agegnehu, Getachew; Moenga, Susan; Desta, Gizaw; Odney, Damaris; Kaushal, Manoj; Bolo, Peter; Korir, Hezekiah; Gebrehawaryat, Yoseph; Singh, Ramesh; Harawa, Rebbie (International Crops Research Institute for the Semi-Arid Tropics, 2025)
The soil microbiome constitutes a critical foundation for terrestrial ecosystem functioning, driving essential processes such as nutrient cycling, organic matter decomposition, and the maintenance of soil structural stability. However, the integrity of these microbial communities is increasingly compromised by agricultural intensification, where heavy reliance on synthetic inputs and tillage leads to biodiversity loss and environmental degradation. To counteract these trends, the B-REAL initiative leverages advanced soil metagenomics to develop regenerative agricultural practices that enhance system resilience.